LITERACY COMPETENCE AND HIGH ORDER THINKING SKILLS IN CURRICULUM 2013 IMPLEMENTATION - Yuliati, Yuyu; Saputra, Dudu Suhandi (Universitas Sebelas Maret, 2018)
The implementation of the curriculum 2013 at the primary and secondary education levels is carried out in order to equip students with complete competencies to face challenges in the 21st century. Therefore, such conditions become special challenges for teachers to prepare superior human resources through the development of literacy and high order thinking skills. This study provides an overview of the development of literacy competence and high order thinking skills in the curriculum 2013 implementation. The results of the study show that literacy competence and higher order thinking skills are demands of the curriculum 2013 development, in which the development is carried out through a learning process that puts students active in scientific work through problem solving activities and involving students in reading habitual activities through school literacy movements.